APLIKASI FUZZY ANALYTICAL HIERARCHY PROCESS DALAM SELEKSI KARYAWAN - Jani Rahardjo; I Nyoman Sutapa (Institute of Research and Community Outreach - Petra Christian University, 2002)
The paper discusses the decision making problem for worker selection. To solved this problem is applied the Fuzzy Analytical Hierarchy Process, development of the ordinary Analytical Hierarchy Process which created to handle the subjectivity of multi-criteria. The best choice by Fuzzy Analytical Hierarchy Process showed that subjectivities criteria have been included comparing by the ordinary Analytical Hierarchy Process. Abstract in Bahasa Indonesia : Makalah ini membahas mengenai masalah pengambilan keputusan untuk memilih alternatif karyawan terbaik. Untuk memecahkan masalah ini digunakan Fuzzy Analytical Hierarchy Process, pengembangan Analytical Hierarchy Process konvensional yang dirancang untuk menangani permasalahan yang kriteria-kriterianya lebih banyak bersifat subjektif. Pilihan karyawan terbaik dengan Fuzzy Analytical Hierarchy Process menunjukkan bahwa subjektifitas kriteria sangat diperhatikan dibandingkan dengan menggunakan Analytical Hierarchy Process konvensional. Kata kunci: Analytical Hierarchy Process, Fuzzy Analytical Hierarchy Process.